2003
DOI: 10.1136/oem.60.10.730
|View full text |Cite
|
Sign up to set email alerts
|

A participatory approach to the study of lifting demands and musculoskeletal symptoms among Hong Kong workers

Abstract: Aims: To investigate the use of a worker based methodology to assess the physical stresses of lifting tasks on effort expended, and to associate this loading with musculoskeletal outcomes (MO). Methods: A cross sectional study was conducted on 217 male manual handling workers from the Hong Kong area. The effects of four lifting variables (weight of load, horizontal distance, twisting angle, and vertical travel distance) on effort were examined using a linguistic approach (that is, characterising variables in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In this study, during the 1-year follow-up, the prevalence of shoulder pain increased from 34% to 41%, and every fourth worker developed a new episode of shoulder pain. Our results are in line with a study of lunch centre workers, one third of whom reported shoulder pain,13 as well as with studies in other occupational populations exposed to shoulder loading work 3 5 6. In our study, shoulder pain was very persistent (or recurrent): 75% of those with pain at baseline had pain 1 year later.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, during the 1-year follow-up, the prevalence of shoulder pain increased from 34% to 41%, and every fourth worker developed a new episode of shoulder pain. Our results are in line with a study of lunch centre workers, one third of whom reported shoulder pain,13 as well as with studies in other occupational populations exposed to shoulder loading work 3 5 6. In our study, shoulder pain was very persistent (or recurrent): 75% of those with pain at baseline had pain 1 year later.…”
Section: Discussionsupporting
confidence: 92%
“…The 1-year prevalence of shoulder pain has varied between studies from 5% to 47% in the general population,2 increasing up to 70% among occupational populations exposed to shoulder loading work 36. Shoulder disorders are often persistent and recurrent, and tend to cause prolonged disability 5 7 8.…”
mentioning
confidence: 99%
“…LEP symptoms were assessed by aggregating questions of pain in one or more of four regions (thigh, knee, lower leg, and ankle). When analyzed separately, the prevalence for thigh (10.2%), leg (34.2%), knee (19.7%), and ankle (14.6%) were similar to those found by Yeung et al [2003] in Chinese manual handling workers, Gurgueira et al [2003] in Brazilian nurses and Nahit et al [2001] in workers of various occupations in England. By walking long distances, pushing their carts without wearing appropriate shoes, and working in a standing position much of the time, the ragpickers would be expected to suffer considerable pressure on their legs and feet.…”
Section: Discussionsupporting
confidence: 76%
“…Self-perceived effort is an integration of multiple factors, including workers' knowledge of their own work environment, their health and well-being, and other non-physical work factors associated with work. Previous studies (Yeung, Genaidy, Deddens, Christin, & Leung, 2003; indicated that personal knowledge and experience can be used to evaluate the physical effort required for various lifting tasks to quantify the physical meaning of lifting task variables at workplaces. However, in this investigation, both exposure (perceived workload) and outcome (low back pain) were assessed by self-reports.…”
Section: Discussionmentioning
confidence: 99%